2022
DOI: 10.3389/fnut.2022.938290
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-cancer Potential of Polysaccharide Extracted From Polygonatum sibiricum on HepG2 Cells via Cell Cycle Arrest and Apoptosis

Abstract: Polygonatum sibiricum is one of the most widely used traditional Chinese medicine in China. Polygonatum sibiricum polysaccharide (PSP) is the main functional component of Polygonatum sibiricum. In this study, a water-soluble polysaccharide (PSP-1) was first isolated from Polygonatum sibiricum with a molecular weight of 38.65 kDa. Structural analysis was performed via methylation and FT-IR spectroscopy analyses, which in combination with NMR spectroscopy, revealed that PSP-1 has a → 4-α-D-Glcp-1 → backbone with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These results revealed that PCP had good anti-fatigue ability. Polygonatum sibiricum extract increased the activity of secondary messengers of cellular aerobic capacity, such as AMPK and p38 [30]. These secondary messengers stimulated the increase in the synthesis of cell mitochondria and antioxidant enzymes, which may have indirectly improved aerobic capacity [31].…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that PCP had good anti-fatigue ability. Polygonatum sibiricum extract increased the activity of secondary messengers of cellular aerobic capacity, such as AMPK and p38 [30]. These secondary messengers stimulated the increase in the synthesis of cell mitochondria and antioxidant enzymes, which may have indirectly improved aerobic capacity [31].…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 cells were cultured in 1640 medium supplemented with 10% fetal bovine serum in a CO 2 incubator set at 37 °C, saturated humidity, and 5% CO 2 [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…PREPS may show long-lasting anti-tumor effects in assisting TNBC therapies through sustaining hematopoiesis and lymphoid regeneration in bone marrow [ 130 ]. In a HepG2 cell, the water-soluble PSP (38.65 kDa) showed concentration-dependent anticancer effects through arresting the cell cycle at the G1 phase, decreasing mitochondrial membrane potential, damaging the nucleus, and inducing cell apoptosis via increasing the activity of caspase-9 and caspase-3 [ 131 ].…”
Section: Applications For Health-promoting Activitiesmentioning
confidence: 99%